Nip in the Bud: A spatiotemporal pattern of soil heavy metals in Chinese herbal medicine planting region and its prevention strategy - Jiale Wang; Qi Yan; Haiyi Mi; Hua Luo; Xinke Zhang; Bashir Ahmad; Baozhong Duan; Jun Zhu; Lin Fang Huang (Ecological Indicators)
Soil heavy metal (HM) pollution and climate change collectively impair the cultivation viability of Chinese herbal medicines (CHM). However, the spatiotemporal pattern of soil HMs in CHM planting (CHMP) region remains uncertain. Here, we extracted concentrations of five HMs (Pb, Cd, Hg, As, and Cu) in CHMP soils, and assessed the national pattern of spatiotemporal distribution of CHMP soils HMs between 2007 and 2024 using the standard deviation ellipse method. The spatial analysis revealed a trend of the gravity center of HMs pollution migrating inland towards the northwest. Furthermore, Cd and Hg exhibit higher ecological risks. The spatial migration of pollution centers differs by metal. The temporal dynamics of five HMs in CHMP regions showed heterogeneity on either side of the HTL. Notably, Cd pollution exhibited a steadily increasing trend during three time periods in the northwest region of the HTL. Moreover, we take Dioscorea opposita Thunb. as an example to evaluate the risks associated with migration under future climate scenarios. The findings showed that climate change is expected to drive the suitable habitats of D. opposita northwestward. Under the SSP245 scenario, the CoM of suitable habitats intersects with the Cd-polluted areas during 2081–2100, posing significant challenges to sustainable cultivation. Given these results, taking a prevention strategy to replan D. opposita planting is necessary. Our study innovatively combines the spatiotemporal variation of soil HMs and MaxEnt modeling to provide a methodological framework that can be utilized by future research endeavors examining the replanment and management of medicinal plants.